Advances in Medical Physics for Regenerative Medicine (Global Journal of Science Frontier Research, 2023)
Globally, the cost of hard tissue repair and regeneration is in the hundreds of billions of dollars every year, and as the population ages, this demand has grown significantly. Structures made of calcium phosphate minerals, such as bone and teeth, are considered to be hard tissues. Techniques for regenerative medicine and smart biomaterial-based tissue engineering have the exciting potential to fill this critical need. By engineering the material's responsiveness to internal or external stimuli, smart biomaterials and constructs can have instructive/inductive, triggering/stimulating, or stimulating effects on cells and tissues. They can also have intelligently tailored properties and functions that can encourage tissue repair and regeneration. Smart scaffolds and stem cell constructs for bone tissue engineering, intelligent medication delivery systems to improve bone regeneration and intelligent dental resins.
Keywords: advanced bio materials; medical physics; regenerative medicine